The Sociological Presentation Of The Issue Of Social Housing - Aali, Hacene; Zerga, Dalila (جامعة الوادي - University of Eloued, 2022)
The Algerian state has worked to improve the standard and lifestyle of the Algerian citizen, especially in the issue of housing. This issue is considered a necessity and an inevitability that is difficult to ignore in Algeria, and this is by focusing on the integration of the efforts of the state, the authorities and institutions as well as the citizen through the most popular formulas, which is social housing, which was given priority in the process of planning and expanding the city of Oran
In Algeria A Field Study Of The City Of Oran
مقال
Keywords: housing politics ; social housing ; protests